Biotechnology, patents and morality a deliberative and participatory paradigm for reform - O'Sullivan, Maureen 1967- (Routledge, 2020)
This book critiques the decision-making process in Article 53(a) of the European Patent Convention. To date, such decisions have been taken at high levels of expertise without much public involvement. The book eschews traditional solutions, such as those found within legislative, judicial and patent office realms and instead develops a radical blueprint for how these decisions can be put to the public. By examining wide-scale models of participatory democracy and deliberation, this book fills a significant gap in the literature. It will be invaluable for patent lawyers, academics, practitioners and intellectual property and patent officials
Based on author's thesis (doctoral - University of Edinburgh, 2018) issued under title: Morality patently matters : the case for a universal suffrage for morally controversial biotechnological patents
General introduction -- In search of a definition of morality in European patent law -- Patent moralities and their traditional adjudications : a critique -- Decision-making in morally controversial biotechnological patent applications -- The participatory budget in Brazil -- Recommendations for reform and conclusion
Keywords: European Patent Convention -- (1973 October 5); LAW / Administrative Law & Regulatory Practice / bisacsh; LAW / General / bisacsh; Biotechnology -- Europe -- Patents; Patent laws and legislation -- Moral and ethical aspects